Factors influencing antenatal mothers choice of hospital for delivery at Hospital Universiti Sains Malaysia (HUSM) and Hospital Kota Bharu (HKB) - S. Zaharah,; M.H. Mohamed Hashim,; A. Mazlan,; T, Winn, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
The objective of this paper is to determine the factors that influence antenatal mothers choice of hospitals for delivery at Hospital Universiti Sains Malaysia (HUSW and Hospital Kota Bharu (HKB). A cross sectional study was conducted on 344 Malays, multiparity antenatal mothers who attended selected Women and Child Health Clinics in Kota Bharu district, from November 2003 to February 2004. Subjects were selected using systematic random sampling. Data were obtained using an interviewer guided, validated and piloted questionnaire. In order to ensure higher inter rater reliability, only one dedicated interviewer was involved. The questionnaire consists of a fav domains namely socio-economic, accessibility, convenience, previous delivery experience, and interpersonal relationship with doctors and nurses, comfort of the patients and their relatives. The data were analyzed using logistic regression. The prevalence ,fir choosing HUSM for delivery center was 38.0% and HKB 62.0% respectively. Based on the univariate logistic regression, nine predictors variables were sign~ficantly associated with the outcomes, namely health center, previous delivery hospital, distance to hospital, accessibility to hospital, good nursing care, short waiting hours, clean wards, and children friendly. Among these only three factors remained significantly influenced when analyzed through multivariate logistic regression. The final model was tested and it was foundfit. The factors derived from the final model were previous delivery hospital, accessibility and children-friendly hospital. Based on the multivariate logistic analysis, this study concludes previous delivery hospital, accessibility and children friendly hospital signficantly influence the choice of hospital for delivery among antenatal mothers in Kota Bharu district.